Tobacco Control Stakeholder Perspectives on the Future of Tobacco Marketing Regulation in Indonesia: A Modified Delphi Study - Putu Ayu Swandewi Astuti; Mary Assunta; Becky Freeman (Korean Society for Preventive Medicine, 2021)
Objectives Tobacco control in Indonesia is very lenient compared to international standards. This study explored the perspectives of tobacco control stakeholders (TCSs) on the likelihood of advancing tobacco marketing regulation in Indonesia. Methods Data were collected from TCSs who were members of the Indonesia Tobacco Control Network group in a modified Delphi study. We collected the data in 2 waves using a questionnaire that comprised a set of closed and open-ended questions. For this paper, we analysed 2 of the 3 sections of the questionnaire: (1) tobacco advertising, promotions, and sponsorship (TAPS) bans, and (2) marketing and retailing regulations. We conducted a descriptive analysis of the scores using Stata/IC.13 and summarised the comments for each item. Results The TCSs viewed the measures/strategies across all aspects of TAPS and tobacco marketing regulation as highly desirable, but provided varied responses on their feasibility. They rated political feasibility lower than technical feasibility for most measures. Advancing TAPS measures and prohibition of selling to minors were considered more attainable by sub-national governments, while prohibition of tobacco corporate social responsibility was considered as the least feasible measure in the next 5 years. Conclusions Despite little optimism for substantial national-level change, there is a positive expectation that sub-national governments will strengthen their tobacco control regulation. It is paramount that the government reduce tobacco industry leverage by implementing Article 5.3 of the World Health Organization Framework Convention on Tobacco Control. Extending advocacy networks beyond tobacco control groups and framing tobacco control more effectively are necessary steps.